1999
DOI: 10.1021/ic9811289
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Dependent Delocalization in Three Isostructural Complexes [LFeNiFeL]2+/3+/4+ (L = 1,4,7-(4-tert-Butyl-2-mercaptobenzyl)-1,4,7-triazacyclononane)

Abstract: The reaction of mononuclear [LFe(III)] where L represents the trianionic ligand 1,4,7-tris(4-tert-butyl-2-mercaptobenzyl)-1,4,7-triazacyclononane with NiCl(2).6H(2)O and subsequent oxidations with [Ni(III)(tacn)(2)](ClO(4))(3) (tacn = 1,4,7-triazacyclononane) and PbO(2)/methanesulfonic acid produced an isostructural series of complexes [LFeNiFeL](n)()(+) (n = 2 (1), n = 3 (2), n = 4 (3)), which were isolated as PF(6)(-) (1, 3) or ClO(4)(-) salts (2). The molecular structures were established by X-ray crystallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 30 publications
1
35
0
2
Order By: Relevance
“…Physical Measurements: UV/Vis/near-IR spectra of CH 3 CN solutions of 1 and 2 were measured on a PerkinϪElmer Lambda 19 Syntheses: The ligand H 3 L · 3 HPF 6 was prepared by following the spectrophotometer in the range 210Ϫ3200 nm at ambient temperapublished procedure for H 3 L · 3 HCl by using an HPF 6 3 OH alternating constant-acceleration spectrometer. The minimal linewidth was 0.24 mm s Ϫ1 (full width at half-height).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Physical Measurements: UV/Vis/near-IR spectra of CH 3 CN solutions of 1 and 2 were measured on a PerkinϪElmer Lambda 19 Syntheses: The ligand H 3 L · 3 HPF 6 was prepared by following the spectrophotometer in the range 210Ϫ3200 nm at ambient temperapublished procedure for H 3 L · 3 HCl by using an HPF 6 3 OH alternating constant-acceleration spectrometer. The minimal linewidth was 0.24 mm s Ϫ1 (full width at half-height).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, both trications have an S t ϭ 1/2 ground state. In order to obtain dition of NaPF 6 , brown microcrystals of [LFeRuFeL]-(PF 6 ) 2 · 3 CH 3 OH (1) were obtained. Recrystallization of a better understanding of their electronic structure, we decided that it would be of value to investigate the isoelec-this material from acetone/acetonitrile (1:1) and addition of Na [BPh 4 ] afforded single crystals of [{LFe} 2 Ru]-tronic heterotrinuclear analogs [LFeRuFeL] 2ϩ/3ϩ .…”
Section: Preparation Of Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] In contrast, no examples of heterometallic vanadium/cobalt or vanadium/nickel thiolato complexes were found in the literature. A series of trinuclear metal complexes of the type [LMMЈML] n+ with L = 1,4,7-tris(4-tertbutyl-2-mercaptobenzyl)-1,4,7-triazacyclononane like [LCoNiCoL] n+ (n = 2-4), [LNiCoNiL] n+ (n = 1-3), [9] [LFeNiFeL] n+ (n = 2-4), [10] [LFeMFeL] n+ (M = Cr, Co; n = 1-3) [11] and [LFeMFeL] n+ (M = Ge, Sn; n = 2,3) [12] have been synthesised and characterised with respect to their magnetic exchange properties. It was shown that in these compounds the mechanism of spin coupling cannot be described exclusively in terms of the classical superexchange mechanisms but rather spin-dependent delocalisation by means of double exchange mechanisms [9] had to be invoked.…”
Section: Introductionmentioning
confidence: 99%